PERSPEKTIF BIRD IN THE HAND: PENENTU DIVIDEND PAYOUT RATIO PERUSAHAAN MANUFAKTUR - Sri Dwi Ari Ambarwati (University of Merdeka Malang, 2014)
This research was specially to test impact of Return On Investments (ROI), Insider Ownership (INSD), Debtto Equity Ratio (DER) to dividend payout ratio (DPR) by the use of free cash flow (FCF) as moderatingvariable on manufacturing firm listed on Indonesian Stock Exchange (ISE) period 2005 until 2011. Thisresearch hypothesized that moderating variable had a positive influence to dividend payout ratio (DPR).Hypothesis testing was done by the use of linear regression model (OLS). Empirical result on panel A (withoutmoderating variable) and panel B (with moderating) were simultaneously ROI, INSD, DER, FCF and moderatedvariable (FCF*ROI) had a significant impact to DPR. Meanwhile panel A showed an evident that DERvariable and FCF had an impact to dividend payout ratio (DPR) and panel B pointed out that DER, FCF,FCF*ROI and FCF*INSD had a significant impact to dividend payout ratio (DPR). Based on moderatedregression analysis (Panel B) FCF as moderating variable had an influence on the relationship between insiderownership and dividend payout ratio (DPR). It was seen in increasing R2 and Adjusted R2 in regression modelbefore being moderated and after. It meant that FCF as moderating variable increased the contribution onmodel one which was proposed.